Sedimentological interpretation and stratigraphical position of glacigenic deposits in the Napęków area (Holy Cross Mountains, Poland) - Ludwikowska-Kędzia, Małgorzata; Pawelec, Halina; Adamiec, Grzegorz (Geologos, 2015)
The identification of depositional conditions and stratigraphical position of glacigenic deposits in the Napęków area is important for the genetic and stratigraphical interpretation of Quaternary deposits in the central part of the Holy Cross Mountains, as well as for a revision of the course and extent of Middle Polish (Saalian) glaciations. These deposits comprise a series of diamictons which occur between sandy-gravelly deposits. Based on results of macro- and microscopic sedimentological investigations, analysis of heavy mineral composition, roundness and frosting of quartz grains, as well as OSL dating, this complex must have formed during the Odranian Glaciation (Drenthe, Saalian, MIS 6). Sandy-gravelly deposits are of fluvioglacial and melt-out origin. Diamictons represent subglacial traction till. Their facies diversity is a result of variations in time and space, complex processes of deposition and deformation, responsible for their formation at the base of the active ice sheet. This glacigenic depositional complex was transformed by erosion-denudation and aeolian processes in a periglacial environment during the Vistulian (Weichselian, MIS 5d-2).